(untitled) (Environmental Smoke, 2024)
The exposure to diesel exhaust particles (DEP) in high-traffic environments is associated with significant alterations in the respiratory system. In parallel, it is assumed that the regular inclusion of compounds containing high levels of polyunsaturated fatty acids, such as pequi oil (Caryocar coriaceum), in the diet may help with disorders caused by these pollutants. The present work investigates the benefits of oral ingestion of fixed oil from Caryocar coriaceum (CC) on lung tissue and ventilatory mechanics in mice exposed to DEP, as well as its chemical composition. The CC, mainly composed of linoleic acid (49.13%), prevented the increase in the bronchoconstriction index and the infiltration of inflammatory cells in the pulmonary alveoli. Moreover, it was able to prevent changes in ventilatory parameters caused by DEP, such as airway resistance, tissue resistance, elastance, lung compliance, inspiratory capacity, and the area of the pressure-volume curve. Our findings demonstrated that the implementation of CC in the diet of mice exposed to DEP was responsible for preventing the establishment of histological and functional alterations in the respiratory system caused by these vehicular pollutants.